Solve: 25x2 − 36 = 0. x = 6, 5 x = −6, −5 x = 36 over 25, x = − 36 over 25 x = 6 over 5, x = − 6 over 5

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

Solve: 25x2 − 36 = 0. x = 6, 5 x = −6, −5 x = 36 over 25, x = − 36 over 25 x = 6 over 5, x = − 6 over 5

Mathematics
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

difference of squares \[\huge\rm a^2-b^2=(a+b)(a-b)\]
take square root of both terms (sqrt of 1st term + sqrt of 2nd term)(sqrt of 1st term - sqrt of 2nd term)

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

I am lost
here is an example if i have 4 i can write it as 2^2 power right ? so what number to the 2 power = 25
5
yes right what about 36 ?
6
right so you can write it as \[\huge\rm 5^2x^2-6^2\] which is same as \[\rm a^2-b^2=(a-b)(a+b)\]
a is first term and b is 2nd term what is a and b in ur equation ?
a=5^2 and b=6^2
not just 5^2 a=5^2x^2 so write it as (a-b)(a+B)
ohh wait
a= 5x b=6 not squares
difference of squares \[\huge\rm\color{reD}{ a}^2-\color{blue}{b}^2=(\color{Red}{a}+\color{blue}{b})(\color{reD}{a}-\color{blue}{b})\]
well guess what its easy to take square roots |dw:1441217018547:dw|
Sorry, @Nnesha I had to do something.
thats fine
let me know what you get :)

Not the answer you are looking for?

Search for more explanations.

Ask your own question